Fifteenth and Sixteenth General Reviews of Quotas-Report of the Executive Board to the Board of Governors. (Policy Papers; Policy Paper ;, 2020)
On January 16, 2020, the Executive Board adopted a Report to the Board of Governors proposing that the Board of Governors adopt a Resolution concluding the Fifteenth General Review of Quotas with no increase in quotas and providing guidance for the Sixteenth General Review of Quotas in line with the IMFC guidance in the October 19, 2019 Communique. The Resolution was adopted by the Board of Governors, effective February 7, 2020, and was designated No. 75-1.